Ultrasonic-assisted process for preparing high-purity glucosamine hydrochloride
Photocatalytic decolorizers are prepared through ultrasonic assisted processes, and the pigments in glucosamine hydrochloride are photocatalyzed by visible light, which solves the problem of saturation of physical adsorbents such as activated carbon, and realizes the preparation of high-purity glucosamine hydrochloride, improving the Productivity and service life.
Patent Information
- Application Number
- CN202411477254.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-14
AI Technical Summary
In the existing preparation methods for glucosamine hydrochloride, physical adsorbents such as activated carbon are easily saturated after decolorization, and complex regeneration processes are required, which are inconvenient to use and low efficiency, resulting in poor purity and appearance quality of glucosamine hydrochloride.
Using ultrasonic assisted process, photocatalytic decolorizers are made through aluminum oxide or aluminum powder, nano titanium dioxide, iron ions and other materials. Visible light is used to photocatalyze the pigment molecules to form a porous structure decolorizer, which can be continuously decolorized without regeneration. Process.
It has achieved high purity preparation of glucosamine hydrochloride, with a pigment removal rate of more than 98%, which has improved production efficiency and service life, avoided the saturation problem of traditional adsorbents, and was convenient and efficient in use.
Smart Images

Figure CN119306774A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glucosamine preparation, and in particular to a process for preparing high-purity glucosamine hydrochloride by ultrasound assistance. Background Art
[0002] Glucosamine hydrochloride is the hydrochloride form of glucosamine (GlcN), and its active ingredient is the glucosamine molecule, which is an essential component for synthesizing proteoglycans in the matrix of articular cartilage. It has the functions of protecting and repairing articular cartilage regeneration and relieving joint pain. One of the preparation methods of glucosamine hydrochloride is the biological extraction method using shrimp and crab shells as raw materials. This method uses concentrated hydrochloric acid to hydrolyze chitin or chitosan in the raw materials into glucosamine, and then obtains the glucosamine hydrochloride product after decolorization, purification, concentration and crystallization. This method has the advantages of a wide source of raw materials and low cost. However, the glucosamine hydrochloride prepared by this method contains a lot of pigments, resulting in poor purity and appearance quality of glucosamine hydrochloride. Although decolorization can be performed by using adsorbents such as activated carbon, since activated carbon separates the pigment from the liquid phase system containing glucosamine hydrochloride by physical adsorption, it loses its decolorization effect when the activated carbon is saturated with adsorption, and it also needs to be regenerated by a special process before it can be reused for decolorization, which is inconvenient to use. Summary of the invention
[0003] In view of the above problems, the present invention provides a process for preparing high-purity glucosamine hydrochloride by ultrasound assistance, wherein the decolorizing agent used in the process can continuously decolorize without the need for a regeneration process, and not only has good reusability, but is also more convenient to use. Specifically, the technical solution of the present invention is as follows.
[0004] A process for preparing high-purity glucosamine hydrochloride by ultrasound assistance comprises the following steps: (1) Alumina or aluminum powder, nano-titanium dioxide, a source of ferric ions or ferrous ions, a binder and water are uniformly mixed and granulated, and then dried to obtain a precursor core.
[0005] (2) Two glass powders with non-overlapping softening temperature ranges, alumina or aluminum powder, a binder and water are mixed evenly to form a slurry. The slurry is then coated on the surface of the precursor core, and then coated with a layer of dry alumina or aluminum powder. After completion, the obtained particles are calcined, and the calcination temperature is between the softening temperature ranges of the two glass powders. After completion, it is cooled to room temperature to obtain a precursor decolorizer.
[0006] (3) The precursor decolorizing agent is placed in water for ultrasonic cleaning and then placed in a strong alkaline solution for ultrasonic treatment. After the treatment, it is placed in water for ultrasonic cleaning again and dried to obtain a photocatalytic decolorizing agent.
[0007] (4) Dissolve the crude glucosamine hydrochloride containing pigment in water to form a saturated solution, then add the photocatalytic decolorizing agent, and then irradiate with visible light under ultrasonic vibration conditions, and then separate the solid and liquid. The obtained liquid phase is precipitated with alcohol, and then the crystals are separated and dried to obtain decolorized and purified glucosamine hydrochloride.
[0008] Furthermore, in step (1), the ratio of the aluminum oxide or aluminum powder, nano titanium dioxide, iron ion or ferrous ion source, and binder is 5-8 parts by weight: 12-17 parts by weight: 0.3-0.6 parts by weight: 4-6.5 parts by weight. The mass ratio of the above components to the water is 1g: 0.18-0.22g.
[0009] Furthermore, in step (1), the source of iron ions or ferrous ions includes at least one of ferric sulfate, ferrous sulfate, ferric nitrate, ferrous nitrate powder, etc.
[0010] Furthermore, in step (1), the drying temperature is 60-75° C. and the drying time is 50-70 min. Optionally, the particle size of the precursor core is 1-3 mm.
[0011] Furthermore, in step (2), of the two softening temperature ranges, the higher temperature range is not less than 880° C., and the lower temperature range is not more than 700° C. The calcination treatment is performed at a temperature of 750-820° C. and for a time of 10-15 min.
[0012] Furthermore, in step (2), the ratio of the glass powder, alumina or aluminum powder, and the binder is 20-30 parts by weight: 6-10 parts by weight: 3.5-7 parts by weight, and the solid content in the slurry is 45-55 wt.%. Optionally, the particle size of the alumina or aluminum powder is 10-40 mesh.
[0013] Furthermore, in step (2), of the two glass powders, the glass powder with a lower softening temperature range is 30-40% of the mass of the glass powder with a higher softening temperature range. Optionally, the particle size of the glass powder is 220-300 mesh.
[0014] Furthermore, in steps (1) and (2), the binder includes at least one of starch, cyclodextrin, etc.
[0015] Furthermore, in step (2), the slurry is 30-38% of the mass of the precursor core.
[0016] Furthermore, in step (3), the ratio of the precursor decolorizing agent to the strong alkali solution is 1 g: 5-20 ml. Optionally, the strong alkali solution includes at least one of a sodium hydroxide solution and a potassium hydroxide solution, and the mass fraction of the strong alkali solution is 10-20%.
[0017] Furthermore, in step (3), the ultrasonic treatment time is 1-1.5 h, and the ultrasonic power is 300-500 W.
[0018] Furthermore, in step (3), the ultrasonic cleaning time is 10-15 minutes, the ultrasonic power is 300-500W, and the cleaning is performed at least three times.
[0019] Furthermore, in step (3), the drying temperature is 70-80° C., and the drying time is 2-2.5 h.
[0020] Furthermore, in step (4), the amount of the photocatalytic decolorizing agent added is 8-15 g / L.
[0021] Furthermore, in step (4), the power of the visible light is 40-70 W, and the bleaching treatment time is 1-2 h.
[0022] Furthermore, in step (4), the alcohol precipitation method is to add 3 to 5 times the volume of ethanol to the liquid phase, stir evenly and then let it stand, and after the precipitated crystals are completely precipitated, separate the crystals and dry them. Optionally, the drying method includes vacuum drying or freeze drying.
[0023] Compared with the prior art, the present invention has at least the following beneficial technical effects: The photocatalytic decolorizing agent prepared by the present invention can utilize visible light to photocatalytically degrade pigment molecules, not only can decolorize continuously, but also does not need to be regenerated after adsorption saturation like traditional physical adsorption decolorizing agents such as activated carbon before it can be used again, and is more convenient and efficient to use. To this end, the present invention uses aluminum oxide or aluminum powder, nano titanium dioxide, iron ions or ferrous ion sources to make a precursor kernel, and then coats the surface of the kernel with two kinds of softening temperature glass powder, aluminum oxide or aluminum powder, and a coating layer formed by a binder, and the coating layer is coated with aluminum oxide or aluminum powder again. After calcination, the binder in the kernel and the binder in the coating layer are removed to form pores. The glass powder with a lower softening temperature forms a porous shell after bonding the glass particles with a higher softening temperature. At the same time, during the calcination process, the iron ions or ferrous ions are doped into the lattice of nano titanium dioxide under the action of high temperature, thereby expanding the response range of nano titanium dioxide to the visible light range, which is convenient for photocatalytic decolorization by irradiation of visible light. In addition, the softened glass particles can also connect the core and the shell together. Further, the present invention places the above-formed precursor decolorant in an alkali solution for ultrasonic treatment, and the aluminum oxide or aluminum powder in the shell is eliminated by the alkali solution to further form a porous shell, and then the alkali solution enters the core to eliminate the aluminum oxide or aluminum powder therein, thereby converting the core into a porous core formed by modified nano titanium dioxide, which is not only convenient for the pigment molecules to enter, but also can well prevent the loss and loss of nano titanium dioxide during use. At the same time, since the shell is a transparent structure, visible light can directly pass through and irradiate the core, thereby photocatalytically degrading the pigment molecules. Since this decolorization method is to completely degrade the pigment molecules into carbon dioxide and water and then eliminate them, it will not be like traditional adsorbents such as activated carbon that only adsorb the pigment molecules in their internal pores. Therefore, the decolorant of the present invention can continue to decolorize without the need for a regeneration process, which significantly improves production efficiency. At the same time, this decolorant of the present invention also has a good mechanical strength sodium reduction model, which greatly improves the service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein: Figure 1 This is a sample diagram of decolorized and purified glucosamine hydrochloride prepared in Example 1 below. DETAILED DESCRIPTION
[0025] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those generally understood by those of ordinary skill in the art to which the present invention belongs. It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present invention. The technical solution of the present invention is now further described by specific implementation.
[0026] Example 1 A process for preparing high-purity glucosamine hydrochloride by ultrasound assistance comprises the following steps: (1) Alumina powder with a particle size of 200 mesh, nano-titanium dioxide, ferric sulfate and cyclodextrin were mixed evenly in a mass ratio of 7:15:0.4:5.5, and then clean water was added to the mixed powder and stirred evenly. The mass ratio of the two was 1g:0.19g. The obtained wet material was granulated and then dried at 70°C for 60 minutes to obtain a precursor core with a particle size of 2~3mm.
[0027] (2) Two glass powders with a softening temperature of about 630-660°C and 910-935°C and a particle size of 280 mesh are mixed evenly to obtain a mixed glass powder, wherein the former glass powder is 33% of the mass of the latter. The mixed glass powder, alumina with a particle size of 20 mesh, and cyclodextrin are mixed at a mass ratio of 27:8:6, and then clean water is added and stirred evenly to obtain a slurry with a solid content of 50%.
[0028] (3) The slurry is mixed with the precursor core to coat the surface of the precursor core with the slurry, and the slurry accounts for 35% of the mass of the precursor core. Then the obtained particles are added to the dry alumina powder for coating. After completion, the obtained particles are heated to 800°C and calcined for 10 minutes. After completion, the particles are cooled to room temperature to obtain the precursor decolorizer.
[0029] (4) The precursor decolorant is ultrasonically cleaned in water for three times, each time for 10 minutes, and the ultrasonic power is 400W. Then the precursor decolorant is filtered out, mixed with a 15% sodium hydroxide solution at a ratio of 1g:10ml, and then ultrasonically treated for 1 hour at an ultrasonic power of 400W. After completion, it is ultrasonically cleaned in water again for three times, each time for 10 minutes, and the ultrasonic power is 400W. Then the solid matter is filtered out and dried at 70°C for 2.5 hours to obtain a photocatalytic decolorant.
[0030] (5) Dissolve the crude product of glucosamine hydrochloride containing pigment into water to form a saturated solution, and then add the photocatalytic decolorizing agent prepared in this example at a dosage of 12 g / L. After completion, irradiate with a 60W fluorescent lamp for 1.5 hours under ultrasonic vibration, and filter out the decolorizing agent after completion. Add 95% ethanol in an amount of 4 times its volume to the obtained liquid phase, stir evenly and let it stand. After the precipitated crystals are completely precipitated, filter out the crystals and vacuum dry them to obtain decolorized and purified glucosamine hydrochloride, such as Figure 1 As shown. Then calculate the pigment removal rate = (η2-η1) / (1-η1), wherein η1 is the purity of the crude glucosamine hydrochloride, and η2 is the purity of the purified glucosamine hydrochloride, and the purity is tested by spectrophotometry. The result of the pigment removal rate is 98.25%.
[0031] Example 2 A process for preparing high-purity glucosamine hydrochloride by ultrasound assistance comprises the following steps: (1) Alumina powder with a particle size of 220 mesh, nano-titanium dioxide, ferrous sulfate and starch were mixed evenly in a mass ratio of 8:17:0.6:6.5, and then clean water was added to the mixed powder and stirred evenly. The mass ratio of the two was 1g:0.22g. The obtained wet material was granulated and then dried at 75°C for 50 minutes to obtain a precursor core with a particle size of 2~3mm.
[0032] (2) Two glass powders with a softening temperature of about 680-700°C and 880-910°C and a particle size of 220 mesh are mixed evenly to obtain a mixed glass powder, wherein the former glass powder is 30% of the latter by mass. The mixed glass powder, alumina with a particle size of 10 mesh, and starch are mixed at a mass ratio of 30:10:7, and then clean water is added and stirred evenly to obtain a slurry with a solid content of 55%.
[0033] (3) The slurry is mixed with the precursor core so that the slurry is coated on the surface of the precursor core. The slurry accounts for 38% of the mass of the precursor core. Then the obtained particles are added to the dry alumina powder for coating. After completion, the obtained particles are heated to 820°C and calcined for 15 minutes. After completion, they are cooled to room temperature to obtain the precursor decolorizer.
[0034] (4) The precursor decolorant is ultrasonically cleaned in water for three times, each time for 15 minutes, and the ultrasonic power is 500W. Then the precursor decolorant is filtered out, mixed with a 20% sodium hydroxide solution at a ratio of 1g:5ml, and then ultrasonically treated for 1 hour at an ultrasonic power of 300W. After completion, it is ultrasonically cleaned in water again for three times, each time for 15 minutes, and the ultrasonic power is 500W. Then the solid matter is filtered out and dried at 80°C for 2 hours to obtain a photocatalytic decolorant.
[0035] (5) Dissolve the crude product of glucosamine hydrochloride containing pigment into water to form a saturated solution, and then add the photocatalytic decolorizing agent prepared in this embodiment at a dosage of 8 g / L. After completion, irradiate with a 70W fluorescent lamp for 1 hour under ultrasonic vibration, and filter out the decolorizing agent after completion. Add 95% ethanol in an amount of 3 times its volume to the obtained liquid phase, stir evenly and let it stand. After the precipitated crystals are completely precipitated, filter out the crystals and vacuum dry them to obtain decolorized and purified glucosamine hydrochloride. Then, the pigment removal rate of this embodiment is calculated using the same method as in the above-mentioned Example 1, and the result is 98.66%.
[0036] Example 3 A process for preparing high-purity glucosamine hydrochloride by ultrasound assistance comprises the following steps: (1) Aluminum powder with a particle size of 300 mesh, nano-titanium dioxide, ferric nitrate and cyclodextrin were mixed evenly in a mass ratio of 5:12:0.3:4, and then clean water was added to the mixed powder and stirred evenly. The mass ratio of the two was 1g:0.18g. The obtained wet material was granulated and then dried at 60°C for 70 minutes to obtain a precursor core with a particle size of 1~2mm.
[0037] (2) Two glass powders with softening temperatures of about 630-660°C and 880-910°C and both with a particle size of 300 mesh are mixed evenly to obtain a mixed glass powder, wherein the former glass powder is 40% of the latter by mass. The mixed glass powder, alumina with a particle size of 40 mesh, and cyclodextrin are mixed evenly in a mass ratio of 20:6:3.5, and then clean water is added and stirred evenly to obtain a slurry with a solid content of 45%.
[0038] (3) The slurry is mixed with the precursor core to coat the surface of the precursor core with the slurry, and the slurry accounts for 30% of the mass of the precursor core. The obtained particles are then added to the dry alumina powder for coating. After completion, the obtained particles are heated to 750°C and calcined for 15 minutes. After completion, the particles are cooled to room temperature to obtain the precursor decolorizer.
[0039] (4) The precursor decolorizer is ultrasonically cleaned in water for three times, each time for 15 minutes, and the ultrasonic power is 300W. Then the precursor decolorizer is filtered out, mixed with a 10% potassium hydroxide solution at a ratio of 1g:20ml, and then ultrasonically treated for 1.5 hours at an ultrasonic power of 300W. After completion, it is ultrasonically cleaned in water again for three times, each time for 15 minutes, and the ultrasonic power is 300W. Then the solid matter is filtered out and dried at 80°C for 2 hours to obtain a photocatalytic decolorizer.
[0040] (5) Dissolve the crude product of glucosamine hydrochloride containing pigment into water to form a saturated solution, and then add the photocatalytic decolorizing agent prepared in this embodiment at a dosage of 15 g / L. After completion, irradiate with a 40W fluorescent lamp for 2 hours under ultrasonic vibration, and filter out the decolorizing agent after completion. Add 95% ethanol in an amount of 5 times its volume to the obtained liquid phase, stir evenly and let it stand. After the precipitated crystals are completely precipitated, filter out the crystals, and freeze-dry them to obtain decolorized and purified glucosamine hydrochloride. Then, the pigment removal rate of this embodiment is calculated using the same method as in the above-mentioned Example 1, and the result is 99.04%.
[0041] Example 4 A process for preparing high-purity glucosamine hydrochloride with ultrasound assistance, which is the same as the above-mentioned embodiment 1, except that the precursor core of this embodiment is prepared by the following method: alumina powder with a particle size of 200 mesh, nano titanium dioxide and cyclodextrin are mixed evenly in a mass ratio of 7:15:5.5, and then clean water is added to the obtained mixed powder and stirred evenly, and the mass ratio of the two is 1g:0.19g. The obtained wet material is granulated, and then dried at 70°C for 60min to obtain a precursor core with a particle size of 2~3mm. Then the pigment removal rate of this embodiment is calculated by the same method as the above-mentioned embodiment 1, and the result is 46.72%.
[0042] Example 5 A process for preparing high-purity glucosamine hydrochloride with ultrasound assistance, which is the same as the above-mentioned embodiment 3, except that the precursor core of this embodiment is prepared by the following method: nano titanium dioxide, ferric nitrate and cyclodextrin are mixed evenly in a mass ratio of 12:0.3:4, and then clean water is added to the obtained mixed powder and stirred evenly, and the mass ratio of the two is 1g:0.18g. The obtained wet material is granulated, and then dried at 60°C for 70min to obtain a precursor core with a particle size of 1~2mm. Then the pigment removal rate of this embodiment is calculated by the same method as the above-mentioned embodiment 1, and the result is 91.38%.
[0043] Example 6 A process for preparing high-purity glucosamine hydrochloride by ultrasound assistance is the same as the above-mentioned embodiment 2, except that the photocatalytic decolorizing agent of this embodiment is prepared by the following method: (1) Alumina powder with a particle size of 220 mesh, nano-titanium dioxide, ferrous sulfate and starch were mixed evenly in a mass ratio of 8:17:0.6:6.5, and then clean water was added to the mixed powder and stirred evenly. The mass ratio of the two was 1g:0.22g. The obtained wet material was granulated and then dried at 75°C for 50 minutes to obtain a precursor core with a particle size of 2~3mm.
[0044] (2) Two glass powders with a softening temperature of about 680-700°C and 880-910°C and a particle size of 220 mesh are mixed evenly to obtain a mixed glass powder, wherein the former glass powder is 30% of the latter by mass. The mixed glass powder, alumina with a particle size of 10 mesh, and starch are mixed at a mass ratio of 30:10:7, and then clean water is added and stirred evenly to obtain a slurry with a solid content of 55%.
[0045] (3) The slurry is mixed with the precursor core so that the slurry is coated on the surface of the precursor core. The slurry accounts for 38% of the mass of the precursor core. Then the obtained particles are added to the dry alumina powder for coating. After completion, the obtained particles are heated to 820°C and calcined for 15 minutes. After completion, they are cooled to room temperature to obtain the precursor decolorizer.
[0046] (4) The precursor decolorant was placed in water and ultrasonically cleaned three times, each time for 15 minutes, and the ultrasonic power was 500 W. Then the precursor decolorant was filtered out and dried at 80° C. for 2 hours to obtain a photocatalytic decolorant. Then the pigment removal rate of this embodiment was calculated using the same method as in the above embodiment 1, and the result was 54.17%.
[0047] Example 7 A process for preparing high-purity glucosamine hydrochloride by ultrasound assistance comprises the following steps: (1) Aluminum powder with a particle size of 300 mesh, nano-titanium dioxide, ferric nitrate and cyclodextrin were mixed evenly in a mass ratio of 5:12:0.3:4, and then clean water was added to the mixed powder and stirred evenly. The mass ratio of the two was 1g:0.18g. The obtained wet material was granulated and then dried at 60°C for 70 minutes to obtain a precursor core with a particle size of 1~2mm.
[0048] (2) Two glass powders with softening temperatures of about 630-660°C and 880-910°C and both with a particle size of 300 mesh are mixed evenly to obtain a mixed glass powder, wherein the former glass powder is 40% of the latter by mass. The mixed glass powder is mixed with cyclodextrin at a mass ratio of 20:3.5, and then clean water is added and stirred evenly to obtain a slurry with a solid content of 45%.
[0049] (3) The slurry is mixed with the precursor core to coat the surface of the precursor core with the slurry, and the slurry accounts for 30% of the mass of the precursor core. The obtained particles are then added to the dry alumina powder for coating. After completion, the obtained particles are heated to 750°C and calcined for 15 minutes. After completion, the particles are cooled to room temperature to obtain the precursor decolorizer.
[0050] (4) The precursor decolorant was ultrasonically cleaned in water for three times, each time for 15 minutes, and the ultrasonic power was 300W. Then the precursor decolorant was filtered out, mixed with a 10% potassium hydroxide solution at a ratio of 1g:20ml, and then ultrasonically treated for 1.5 hours at an ultrasonic power of 300W. After completion, it was ultrasonically cleaned in water again for three times, each time for 15 minutes, and the ultrasonic power was 300W. Then the solid matter was filtered out and dried at 80°C for 2 hours to obtain a photocatalytic decolorant. Then the pigment removal rate of this embodiment was calculated using the same method as in the above-mentioned Example 1, and the result was 83.56%.
[0051] Example 8 A process for preparing high-purity glucosamine hydrochloride by ultrasound assistance comprises the following steps: Dissolve the crude product of glucosamine hydrochloride containing pigment in water to form a saturated solution, then add the step (5) of the above embodiment 1 at a dosage of 12 g / L to filter out the decolorizing agent. After completion, irradiate with a 60W fluorescent lamp for 1.5 hours under ultrasonic vibration, and after completion, filter out the decolorizing agent. Add 95% ethanol in an amount of 4 times its volume to the obtained liquid phase, stir evenly and let stand, filter out the crystals after the precipitated crystals are completely precipitated, and vacuum dry them to obtain decolorized and purified glucosamine hydrochloride. Then use the same method as the above embodiment 1 to calculate the pigment removal rate of this embodiment, and the result is 98.21%.
[0052] Example 9 A process for preparing high-purity glucosamine hydrochloride by ultrasound assistance comprises the following steps: The crude product of glucosamine hydrochloride containing pigment is dissolved in water to form a saturated solution, and then the decolorant filtered out after irradiation for 1.5 hours of the above-mentioned embodiment 8 is added in an amount of 12g / L. After completion, irradiate with a 60W fluorescent lamp for 1.5 hours under ultrasonic oscillation, and filter out the decolorant after completion. Add 95% ethanol with 4 times its volume to the obtained liquid phase, stir and let stand, filter out the crystals after the crystals precipitated are completely precipitated, and vacuum dry to obtain the decolorized and purified glucosamine hydrochloride. Then the pigment removal rate of the present embodiment is calculated using the same method as in the above-mentioned embodiment 1, and the result is 98.13%.
[0053] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A process for preparing high-purity glucosamine hydrochloride by ultrasound assistance, characterized in that: The steps include: (1) Alumina or aluminum powder, nano-titanium dioxide, a source of ferric ions or ferrous ions, a binder and water are uniformly mixed and granulated, and then dried to obtain a precursor core; (2) Two glass powders with non-overlapping softening temperature ranges, alumina or aluminum powder, a binder and water are mixed evenly to form a slurry; the slurry is then coated on the surface of the precursor core, and then coated with a layer of dry alumina or aluminum powder. After completion, the obtained particles are calcined, and the calcination temperature is between the softening temperature ranges of the two glass powders; after completion, the precursor is cooled to room temperature to obtain a precursor decolorizer; (3) placing the precursor decolorizing agent in water for ultrasonic cleaning and then placing it in a strong alkaline solution for ultrasonic treatment. After completion, placing it in water for ultrasonic cleaning again and drying to obtain a photocatalytic decolorizing agent; (4) Dissolving the crude product of glucosamine hydrochloride containing pigment into water to form a saturated solution, then adding the photocatalytic decolorizing agent, and then irradiating it with visible light under ultrasonic vibration conditions, and then separating the solid and liquid after completion; precipitating the obtained liquid phase with alcohol, and then separating the crystals and drying them to obtain decolorized and purified glucosamine hydrochloride.
2. The process for preparing high-purity glucosamine hydrochloride by ultrasound assistance according to claim 1, characterized in that: In step (1), the ratio of the aluminum oxide or aluminum powder, nano-titanium dioxide, iron ion or ferrous ion source, and binder is 5-8 parts by weight: 12-17 parts by weight: 0.3-0.6 parts by weight: 4-6.5 parts by weight; the mass ratio of the above components to the water is 1g: 0.18-0.22g.
3. The process for preparing high-purity glucosamine hydrochloride with ultrasound assistance according to claim 1, characterized in that: In step (1), the source of iron ions or ferrous ions includes at least one of ferric sulfate, ferrous sulfate, ferric nitrate, and ferrous nitrate powder; Optionally, in step (1), the drying temperature is 60-75°C and the drying time is 50-70 minutes; Optionally, in step (1), the particle size of the precursor core is 1-3 mm.
4. The process for preparing high-purity glucosamine hydrochloride with ultrasound assistance according to claim 1, characterized in that: In step (2), of the two softening temperature ranges, the higher temperature range is not less than 880°C, and the lower temperature range is not more than 700°C; the temperature of the calcination treatment is 750-820°C, and the time is 10-15 minutes.
5. The process for preparing high-purity glucosamine hydrochloride with ultrasound assistance according to claim 1, characterized in that: In step (2), the ratio of the glass powder, alumina or aluminum powder, and the binder is 20-30 parts by weight: 6-10 parts by weight: 3.5-7 parts by weight, and the solid content in the slurry is 45-55wt.%; optionally, the particle size of the alumina or aluminum powder is 10-40 mesh; Optionally, in step (2), of the two glass powders, the glass powder with a lower softening temperature range is 30-40% of the mass of the glass powder with a higher softening temperature range; Optionally, in step (2), the particle size of the glass powder is 220-300 mesh.
6. The process for preparing high-purity glucosamine hydrochloride with ultrasound assistance according to claim 1, characterized in that: In steps (1) and (2), the binder includes at least one of starch and cyclodextrin.
7. The process for preparing high-purity glucosamine hydrochloride with ultrasound assistance according to claim 1, characterized in that: In step (2), the slurry is 30-38% of the mass of the precursor core.
8. The process for preparing high-purity glucosamine hydrochloride with ultrasound assistance according to claim 1, characterized in that: In step (3), the ratio of the precursor decolorizing agent to the strong alkaline solution is 1g: 5-20ml; Optionally, in step (3), the strong alkaline solution includes at least one of a sodium hydroxide solution and a potassium hydroxide solution; Optionally, in step (3), the mass fraction of the strong alkaline solution is 10-20%; Optionally, in step (3), the ultrasonic treatment time is 1-1.5 h, and the ultrasonic power is 300-500 W; Optionally, in step (3), the ultrasonic cleaning time is 10-15 min, the ultrasonic power is 300-500 W, and the cleaning is performed at least three times; Optionally, in step (3), the drying temperature is 70-80° C. and the drying time is 2-2.5 h.
9. The process for preparing high-purity glucosamine hydrochloride with ultrasound assistance according to claim 1, characterized in that: In step (4), the amount of the photocatalytic decolorizing agent added is 8-15 g / L.
10. The process for preparing high-purity glucosamine hydrochloride with the assistance of ultrasound according to any one of claims 1 to 9, characterized in that: In step (4), the power of the visible light is 40-70 W, and the decolorization treatment time is 1-2 h; Optionally, in step (4), the alcohol precipitation method is to add 3 to 5 times the volume of ethanol to the liquid phase, stir evenly and then let it stand, and after the precipitated crystals are completely precipitated, separate the crystals and dry them.